Color element: perception, presence, representation - Hipólito, Rodrigo (Revista do Colóquio, 2023)
In its 22nd issue, Revista do Colóquio presents works that expose processes, critical analyzes and historical narratives in different contexts linked to the perception, representation and presence of color in works of art, with its most diverse poetic, philosophical, anthropological, sociopolitical and cultural. In addition to the texts included in the theme that gives this edition its title, we present articles, experience reports, visual essays, reviews and translations of free themes.